Factors affecting the CO2 emissions, cost efficiency and eco-strength efficiency of concrete containing rice husk ash: A database study. (4th April 2022) - Ozturk, Ece; Ince, Ceren; Derogar, Shahram; Ball, Richard
Highlights: Inadequacies in the disposal methods lead disruptive environmental deprivation. Database approach is used to assess the RHA utilisation in concrete for first time. Boundary conditions played a key role in sustainability performance of RHA concrete. The use of RHA and pozzolans in concrete could reduce the carbon footprint by 25%. RHA incorporation in concrete offers a greener disposal lane for agricultural wastes. Abstract: The agriculture industry has grown dramatically by about three times over the last 50 years due to the rapid population growth, improvements in green production technology and agricultural land development. Rice is the second most-consumed agricultural product globally. The rice husk ash (RHA), attained by burning the husk that is removed in the process of rice production, possesses high pozzolanic activity and therefore is a promising supplementary cementitious material. Despite the numerous studies on the successful incorporation of RHA in concrete in the literature, a comprehensive assessment on the sustainability aspects of these practices has not yet been solely and exclusively addressed. The paper reports findings from the analysis of a large database on the RHA incorporation in concrete. Principal sustainability components such as CO2 emissions, cost efficiency and eco-strength efficiency are described. The database, comprising over 1000 data points has been utilized to assess the key factors that have significant influences on the mechanical properties of concrete comprising RHA using the established set of criteria. Independent determination of the boundary conditions played a vital role in the sustainability assessment. The results showed that the use of RHA along with the other pozzolanic materials can yield a 25% diminution in the CO2 emissions generated during the concrete production in conjunction with a 65% rise in the cost efficiency of such practices. The findings reported in this study demonstrate improved sustainability for construction practice and highlight greener waste management routes that can be established for RHA.